A techno-economical study on medium density fiberboard using napier grass fiber as ceiling board - Abu Bakar, Norrahim; Azni, Mohd Edyazuan; Hameed Sultan, Mohamed Thariq; Ariffin, Ahmad Hamdan (Centre for Advanced Research on Energy, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2017)
This project is about extraction of bast fiber from Napier grass which is known as Pennisetum purpereum. The purpose of this research is to produce Medium Density Fiberboard board with density of 350kg/m³ using natural fiber and to investigate the optimum properties towards the application as ceiling board. Napier grass fiber board has values resulted at Modulus of rupture (MOR) is 2.90GPa and Modulus of elastic (MOE) is 39.03MPa. Water absorption (WA) at 27.83% and thickness swelling (TS) at 6.67% with thermal conductivity (λ) value is 0.044W/mK. This fiberboard can be an insulation which contributes to save production cost, less hazardous, low environmental footprint and a new innovation.